Pendampingan Pembuatan Desain Kawasan Pariwisata Berbasis CBT (Community Based Tourism) Bagi Pokdarwis Di Kawasan Danau Gedang Kabupaten Bengkulu Tengah - Dwi Oktavallyan; Samsul Bahri; Recky Yundrismein (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
One of the tourist attractions which is loved Bengkulu local tourists is The Gedang Lake Tourist Area. The Gedang Lake is located in Padang Betuah Village, Pondo Kelapa District, Bengkulu Tengah Regency. Gedang Lake has been a tourism potential which is quite interesting. This lake offering views is not found in another place because of the specialty of this lake directly opposite the Indian Ocean Coast. But the amazing lake not directly proportional tothe facilities offered. Supporting facilities in a tour that is located on the lake is still relatively minimal. Kelompok Sadar Wisata (POKDARWIS) started the first step to arrange this area but it's still not optimal. For the manufacture mentoring activities Designing CBT (Community Based Tourism) Facilities for POKDARWIS in The Gedang Lake Tourist Area need to be done. The methods used were counseling, discuss, observation, and manufacture mentoring activities Designing CBT. Produced output is layout from lake tourism facilities and one of the models artificial attraction in Gedang Lake Tourism. This activity is expected to be able to facilitate tourism development in Gedang Lake and to given information about tourism for Tourism Aware Groups and can encourage increasing numbers of tourists.